2004
DOI: 10.1007/bf03347494
|View full text |Cite
|
Sign up to set email alerts
|

Prior gestational hyperglycemia: A long-term predictor of the metabolic syndrome

Abstract: Little is known about the association between prior gestational hyperglycemia of different severity and the subsequent risk for the metabolic syndrome. Eighty-one women with prior gestational diabetes mellitus (GDM), 25 with one abnormal value at the oral glucose tolerance test (OGTT), and 65 with normal OGTT were studied after a mean of 8.5 yr from the index pregnancy. Patients with prior gestational hyperglycemia (both one abnormal value at the OGTT and GDM) showed a worse metabolic pattern than subjects wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 36 publications
3
49
0
Order By: Relevance
“…The higher proportion of self-reported medically treated hypertension and dyslipidemia in the GDM women compared with the controls is in line with previous studies (6,7,8). In this study, the prevalence of abnormal lipid concentrations was remarkably high in both groups and unexpectedly, it tended to be higher in the control group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The higher proportion of self-reported medically treated hypertension and dyslipidemia in the GDM women compared with the controls is in line with previous studies (6,7,8). In this study, the prevalence of abnormal lipid concentrations was remarkably high in both groups and unexpectedly, it tended to be higher in the control group.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have indicated that history of GDM increases the risk of metabolic syndrome (MS) and cardiovascular diseases (CVD), especially when it is associated with obesity, increased fasting glucose concentration, and excessive weight gain during pregnancy (6,7,8,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Women with previous GDM had a 3-fold higher risk of metabolic syndrome compared to non-GDM controls (Lauenborg et al, 2005). A similar study in Europe reported prevalences of metabolic syndrome of 21% and 4.6%, respectively, 8.5 years' postpartum (Bo et al, 2004b). Indeed, prior gestational hyperglycemia in the absence of fulfilling the overt criteria for GDM results in a future risk of metabolic syndrome 2-4 times that of those with normoglycemia in pregnancy.…”
Section: Development Of Metabolic Syndrome After Gdmmentioning
confidence: 87%
“…This risk is 10 times higher in women with concomitant pre-pregnancy obesity (Bo et al, 2004a). Thus, even mild gestational hyperglycemia predicts metabolic syndrome (Bo et al, 2004b), and metabolic syndrome is increasingly more likely to develop over time following the index pregnancy (Bo et al, 2006). These studies highlight the chronic nature of the metabolic dysfunction associated with GDM.…”
Section: Development Of Metabolic Syndrome After Gdmmentioning
confidence: 96%
“…Women with GDM have been reported to have increased rates of stillbirth, polyhydramnios, gestational hypertension, macrosomia, and cesarean delivery (9). GDM usually resolves after delivery, but it appears that the risk of recurring GDM and type 2 diabetes mellitus are increased in subsequent pregnancies, along with cardiovascular risk later in life (10,11). Although the precise role of the risk factors related to GDM (multiparity, obesity,) has not yet been entirely defined, they may be included in the classification of pregnancy-related or maternal factors (12).…”
Section: Discussionmentioning
confidence: 99%